Sistem Antrian Konsultasi Dokter Praktik Menggunakan Single Channel Single Phase Berbasis Website - Fani Fadilah; Jumadil Nangi; Rizal Adi Saputra (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2023)
In digital era, development of information technology is unavoidable, almost all sectors have utilized development of information technology to facilitate all human activities, including health agencies. One form of health agency is a clinic. Sometimes in clinics, there is still way to take the queue number manually, thus making queue so long. Based on these problems, queuing system is needed to solve all queuing problems. In this study, used Single Channel Single Phase where Single Channel is service system that has one service, while Single Phase is only having one service station so after receiving service, it can immediately exit queue system. Based on results of the study, conclusions were obtained: The system built has been successfully implemented Single Channel Single Phase method where this success parameter can be seen from system that provides information about the queue that is running so that the waiting time for patients is more efficient. The characteristics of queuing that occur in Mono Valensi clinic with one stage of service show that average queue in system is ± 2 people, average queue is ± 4 people, average waiting time in system is ± 63 minutes, average waiting time in queue is ± 108 minutes.